2011
DOI: 10.1124/dmd.111.039297
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Cytochrome P450 Activity and the Effect of 1-Aminobenzotriazole on Hepatic Transport in Sandwich-Cultured Human Hepatocytes

Abstract: ABSTRACT:Sandwich-cultured human hepatocytes (SCHH) have been widely used for in vitro assessments of biliary clearance. However, the modulation of metabolism enzymes has not been fully evaluated in this system. The present study was therefore undertaken to determine the activity of cytochrome P450 (P450) 1A2, 2C8, 2C9, 2C19, 2D6, and 3A and to evaluate the impact of 1-aminobenzotriazole (ABT) on hepatic uptake and biliary excretion in SCHH. The SCHH maintained integrity and viability as determined by lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…To eliminate hepatocyte metabolism of the PIs, all SCHH were pre‐incubated with 5 mM ABT for 1 h before conducting the transport studies, and the lack of hepatocyte metabolism of the 3 H‐PIs via LC/UV coupled with radioactivity fractionation was confirmed. Previous studies conducted in human liver microsomes and hepatocytes showed that pre‐incubation with ABT (> 2 mM), a potent CYP inactivator, can effectively abolish the activities of multiple CYPs . In addition, ABT does not appear to be an inhibitor of the transporters expressed in the human hepatocytes, as Kimoto et al .…”
Section: Discussionmentioning
confidence: 93%
“…To eliminate hepatocyte metabolism of the PIs, all SCHH were pre‐incubated with 5 mM ABT for 1 h before conducting the transport studies, and the lack of hepatocyte metabolism of the 3 H‐PIs via LC/UV coupled with radioactivity fractionation was confirmed. Previous studies conducted in human liver microsomes and hepatocytes showed that pre‐incubation with ABT (> 2 mM), a potent CYP inactivator, can effectively abolish the activities of multiple CYPs . In addition, ABT does not appear to be an inhibitor of the transporters expressed in the human hepatocytes, as Kimoto et al .…”
Section: Discussionmentioning
confidence: 93%
“…Data obtained from specific chemical inhibitor studies in human liver microsomes (HLM) are also used to corroborate the estimates of f m obtained with rCYPs. The CL int estimate obtained in HLM is generally compared with CL int determined in human hepatocytes incubated with and without 1-aminobenzotriazole to determine if other metabolic pathways could contribute to reducing the estimates of f m CYP (Emoto et al, 2010;Kimoto et al, 2012a). It is important to recognize that the predicted clinical DDI (AUCR) is very sensitive when the estimates of f m by one particular metabolic route or enzyme exceed 0.8-0.9, and it is therefore important to account for all possible metabolic pathways (Fig.…”
Section: Predicting Drug-drug Interactionsmentioning
confidence: 99%
“…The hepatotoxic effect of Ro 47-8634 also tended to disappear in human hepatocytes pretreated with 1-ABT, although the recovery was not statistically significant. This may arise through the weak inactivation potential of 1-ABT for CYP2C9 compared with other P450 isoforms (Kimoto et al, 2012). On the other hand, ETM-mediated specific CYP3A inhibition did not affect the cytotoxicity induced by Ro 47-8634.…”
Section: Discussionmentioning
confidence: 81%